2005
DOI: 10.1055/s-2005-837696
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and Lipid Alterations Induced by Cadmium in Tomato (Lycopersicon esculentum) Chloroplast Membranes

Abstract: The effects of cadmium (Cd) uptake on ultrastructure and lipid composition of chloroplasts were investigated in 28-day-old tomato plants (Lycopersicon esculentum var. Ibiza F1) grown for 10 days in the presence of various concentrations of CdCl2. Different growth parameters, lipid and fatty acid composition, lipid peroxidation, and lipoxygenase activity were measured in the leaves in order to assess the involvement of this metal in the generation of oxidative stress. We first observed that the accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 49 publications
7
72
1
6
Order By: Relevance
“…However, the percentage of palisade tissue, palisade thickness and cell area increased in Salix fragilis exposed to Cd. In our study, the decrease of palisade cell area observed in the Populus × euramericana clone is in agreement with the findings of Djebali et al (2005), who reported a reduction of mesophyll cell size, reduced intercellular spaces, and severe alterations of chloroplast fine structure in tomato upon Cd exposure. Furthermore, Cd treatment affected adaxial epidermis cell size only in the Populus × euramericana clone.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 93%
See 1 more Smart Citation
“…However, the percentage of palisade tissue, palisade thickness and cell area increased in Salix fragilis exposed to Cd. In our study, the decrease of palisade cell area observed in the Populus × euramericana clone is in agreement with the findings of Djebali et al (2005), who reported a reduction of mesophyll cell size, reduced intercellular spaces, and severe alterations of chloroplast fine structure in tomato upon Cd exposure. Furthermore, Cd treatment affected adaxial epidermis cell size only in the Populus × euramericana clone.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 93%
“…Cd causes structural and functional alterations in photosynthetic apparatus, resulting in reduced or inhibited photosynthesis (Parmar et al 2013). Furthermore, Cd toxicity may provoke an increase in peroxidation of chloroplast membrane lipids by enhancement of lipoxygenase activity, resulting in disorganization of thylakoid membranes and decreased concentration of both chlorophylls and carotenoids (Djebali et al 2005). High Cd concentrations in plant tissues can also affect other physiological processes, such as water regime, mineral nutrient uptake and ion metabolism (Parmar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It can be also associated with a microtubules disruption which may alter the shape and the synthesis of cell wall caused by the action of Pb (LIU et al, 2009). Chloroplast changes observed in cells of M. arvensis treated with Pb were already described in Potamogeton crispus treated with Pb, resulting in dilation of chloroplasts and disruption of their membranes (HU et al, 2007), possibly by reducing the concentration of membrane lipids caused by contamination with Pb as noted in the chloroplasts of Lycopersicon esculentum leaves (DJEBALI et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…The reduced production of H 2 O 2 and lipid peroxidation in calcium-treated plants suggest the potential of calcium in reversing ROSinduced oxidative damage. The increased peroxidation of membrane lipids in cadmium-stressed plants is due to the increased lipoxygenase activity, which results in the rapid generation of peroxides and hydroxyl radicals and thus imposes deteriorating effects on cellular organelles (Djebali et al 2005). Recently, it was demonstrated that the application of calcium to cadmium-stressed mustard (Ahmad et al 2015) and faba bean (Siddiqui et al 2012) plants caused significant reductions in lipid peroxidation by downregulating the production rates of ROS.…”
Section: Discussionmentioning
confidence: 99%